Peningkatan Akurasi Perhitungan Kapasitas Dukung Pondasi Strauss melalui Integrasi Profil Diameter Aktual Sepanjang Tiang - Heni Agnes Rosyta; Agata Iwan Candra (Jurnal Talenta Sipil, 2026)
Vertical variability in layered soil profiles often influences the load-bearing performance of pile foundations, particularly for Strauss piles, which exhibit non-uniform diameters and are affected by manual drilling processes. This study aims to evaluate the relationship between depth, depth–diameter ratio (D/B), ultimate bearing capacity (Qu), and allowable bearing capacity (Qall) for B50 and B60 piles based on empirical estimations and field test results. The methodology includes cone penetration resistance (Qc) analysis, bearing capacity calculation using the Meyerhof approach, and field testing to obtain actual Qu and Qall values. The results show that bearing capacity increases with depth until approximately 4.0 m before changing at subsequent depths, with field-measured Qu values remaining lower than empirical predictions, exhibiting differences of 16.993% for B50 and 17.713% for B60. Allowable bearing capacity demonstrates a similar trend, where Meyerhof predictions consistently exceed field measurements. Analysis based on D/B ratios also reveals a consistent pattern of increasing capacity toward a critical ratio followed by changes at larger ratios. Overall, the findings indicate that depth and D/B ratio are dominant parameters controlling the bearing performance of Strauss piles in layered soil conditions.